Treatment of Oral Pyogenic Granuloma by 810 nm Diode Laser - Mahmood, Ali S. (Iraqi Journal of Laser, 2008)
Pyogenic granuloma is one of the inflammatory hyperplasia seen in the oral cavity. Thepresent study included 10 patients with pyogenic granuloma, involving 4 males and 6 females with 1:1.5male to female ratio. Patient ages ranged from 5 to 85 years (mean, 30 years) and half of the lesions hadpedunculated base, with surface ulceration in 10% of cases. Treatment consisted of resection, using 810nm diode lasers. Eight patients were anesthetized during the surgical operation by local infiltration ofanesthesia. Only three patients reported mild post-operative pain within the first 24 hours of the healingperiod. During the surgical operation there was no significant bleeding so clear surgical field. There wasno bleeding postoperatively. There was mild edema appear in first 2 days after the surgery, and then itsubsided gradually. There was no infection in all the patients treated. One day following the operationthe intra oral examination showed dark-brown necrotic tissue, friable with red inflamed line around theedges. After five days, the observation revealed that the sloughs tissue was completely changed to whitecolor and was easily removed by gauze. Wound healing was excellent after only one week. All thesamples were diagnosed histopathologically as pyogenic granuloma.